A set of BAC clones spanning the human genome - Krzywinski, Martin (Oxford University Press, 2004)
Using the human bacterial artificial chromosome (BAC) fingerprint-based physical map, genome sequence assembly and BAC end sequences, we have generated a fingerprint-validated set of 32 855 BAC clones spanning the human genome. The clone set provides coverage for at least 98% of the human fingerprint map, 99% of the current assembled sequence and has an effective resolving power of 79 kb. We have made the clone set publicly available, anticipating that it will generally facilitate FISH or array-CGH-based identification and characterization of chromosomal alterations relevant to disease.